Preparing the use of English skills for careers in the tourism industry at the Faculty of Economics and Tourism, Soupanouvong University - MIXAYKONE, Khanthaly; MANIVONG , Phim; BOUNTHAVONG , Oudalon; KASEUMSOUK, Amphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objective of this research aimed to find out the preparing the use of English skills for careers in the tourism industry at the Faculty of Economic and Tourism Management (FET), Souphanouvong University (SU). The research consisted of five chapters and the instrument used was a questionnaire which included 60 items to collect quantitative data to find the experiences in using English skills of students, the use of English skills for careers in the tourism industry, and the possible ways for improving in using English skills of students with the total 312 participants who studied at Economics, General business administration, Tourism, Finance and Accounting. The data was analyzed by using program SPSS for Windows (Version 17 and Microsoft Excel 2017) to analyze information for frequency, average into percentage, mean value and standard deviation (S.D) of this research project. The results of this research revealed that collecting quantitative data from students at the Faculty of Economic and Tourism Management (FET). The sample group were students from Economics, General business administration, Tourism, and Finance and Accounting Departments at the FET. The Analysis of the data illustrated that the students at the Faculty of Economics and Tourism had a positive preparing towards speaking, listening, reading, and writing for the use of English skills for careers in the tourism industry at FET, SU. However, writing skill is lowest impression from both the situation of using English skills of students and preparing the use of English skills for careers in the tourism industry. In addition, the suggestion to the possible ways for improving in using English skills of students; reading skill is also lowest impression from the four skills.